If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -12 = 7x + -8 + 8x + -1 Reorder the terms: -12 + 18x = 7x + -8 + 8x + -1 Reorder the terms: -12 + 18x = -8 + -1 + 7x + 8x Combine like terms: -8 + -1 = -9 -12 + 18x = -9 + 7x + 8x Combine like terms: 7x + 8x = 15x -12 + 18x = -9 + 15x Solving -12 + 18x = -9 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -12 + 18x + -15x = -9 + 15x + -15x Combine like terms: 18x + -15x = 3x -12 + 3x = -9 + 15x + -15x Combine like terms: 15x + -15x = 0 -12 + 3x = -9 + 0 -12 + 3x = -9 Add '12' to each side of the equation. -12 + 12 + 3x = -9 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = -9 + 12 3x = -9 + 12 Combine like terms: -9 + 12 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 9p+8=10+7 | | A+b+c=180forx | | -8(1-7b)=-400 | | 3+6x+6x=-9 | | 21=17x-10x | | 6y-5-2y+4=0 | | 12-2b=7 | | 6y-5-2t+4=0 | | 32x-22=-4(1-8x) | | 12b-2=7 | | s+2.5s+20=55 | | 2x=2x+2x | | 11+5q=12+4q | | 6(t+5)=5(1+t)-5 | | 7v=8.75 | | 4=-(p-5) | | -13(-8x+7)-3=14(x+19) | | f-v=f+yx | | 7(3+v)+34v=15v | | -2+11=m-6 | | 3(x-4)=8+7x | | 23+11+2c=10-2c | | 20x+5x=15 | | 1200+40x=3000 | | -2-7b=12 | | 18t^2+18-32t^3=0 | | 2(2x+3)+-2=5 | | -2b-7=12 | | 3(8m-13)+10=17(3+2m) | | 10+2m=16 | | 2(2x+3)-2=2 | | (x*x)-3x=0 |